Age group determines the acceptability of protein derived off-flavour. (July 2021) - Lester, Sophie; Cornacchia, Leonardo; Corbier, Camille; Hurst, Katherine; Ayed, Charfedinne; Taylor, Moira A.; Fisk, Ian
Highlights: Heat-treatment of protein ingredients can impart sulfurous flavours into beverages. Sulfurous flavours negatively impacted consumer acceptance of a dairy beverage. Older adults had greater acceptance of sulfurous flavours compared to younger adults. Diacetyl reduced the negative impact of these compounds for both age groups. Best estimate thresholds give a conservative estimate of off-flavour acceptability. Abstract: Many older adults fail to meet their daily protein requirements, potentially due to social, physical and medical factors, including sensory and appetite changes. Additionally, our previous research has identified potential sulfurous off-flavours, originating from heat-treatment of protein ingredients, which could play a role in consumer acceptance. This study aims to determine the hedonic impact of these potential off-flavours when added to a dairy beverage, identify the specific off-flavour concentrations which cause rejection by consumers, and lastly investigate difference in acceptance between older and younger consumers. A rejection threshold (RjT) protocol was used, in combination with Best Estimate Thresholds (BET), whereby sulfurous flavours (dimethyl sulfide, dimethyl disulfide and dimethyl trisulfide), and diacetyl were added to create a range of concentrations. 95 participants (younger n = 49, 18–38 years; older n = 46, 60–79 years) tasted 7 pairs of samples (one blank and one with ascending off-flavour concentration) and selected their preferred samples. Sulfurous flavours negatively impacted consumer acceptance, however, the extent to which they impart a negative effect differs between age groups. Younger adults rejected samples containing low concentrations of sulfurous off-flavours (1.55 ppb), however, older adults rejected samples with concentrations over 3 times higher (5.08 ppb). When combined with sulfurous flavours, diacetyl increased the rejection threshold for both groups. In conclusion, these observations imply that a greater quantity of off-flavour may be present before acceptance is reduced in the older consumer group. Moreover, diacetyl demonstrates partial masking abilities of sulfurous off-flavours, and BET gave a more conservative estimate of acceptability. This knowledge will help guide sensory innovation of high-protein beverages for older consumers to support product acceptance and optimal intake.